Pemanfaatan Terbitan Berkala oleh Mahasiswa di Perpustakaan Politeknik Negeri Medan - Hutasuhut, Febri Dwi Sasmita; Dalimunthe, Muhammad; Syam, Abdi Mubarak (Comit: Communication, Information and Technology Journal, 2025)
This research discusses the "Utilization of Periodical Publications by Students at the Library of Politeknik Negeri Medan." The study was conducted at the Library of Politeknik Negeri Medan. The aim of this research is to identify the periodical publication collections, understand their utilization, and recognize the obstacles or challenges faced by users in utilizing these collections. The research utilized a descriptive method with a qualitative approach. Data collection techniques included interviews, observations, and documentation. Data analysis was conducted through three stages: data reduction, presentation, and conclusion drawing. The findings indicate that the existing periodical publication collections have been utilized by patrons in their daily activities to search for references to fulfill academic assignments. However, obstacles and challenges in utilizing these collections include incomplete collections, limited user knowledge about periodical publications, and insufficient library promotion at the Library of Politeknik Negeri Medan.